Head‐to‐head comparison of the pharmacokinetic profiles of a high‐purity factor IX concentrate (AlphaNine®) and a recombinant factor IX (BeneFIX®) in patients with severe haemophilia B. (7th May 2013) - Lissitchkov, T.; Matysiak, M.; Zavilska, K.; Laguna, P.; Gercheva, L.; Antonov, A.; Moret, A.; Caunedo, P.; Aznar, J. A.; Woodward, M. K.; Páez, A.
Summary: Head‐on comparative studies of factor IX (FIX) concentrates performed under standardized conditions are rarely conducted regardless of being a valuable instrument guiding health care providers towards better informed and cost‐effective decisions. This study is an extension of a multicentre study that assessed the efficacy, safety and pharmacokinetics (PK) of AlphaNine ® in 25 previously treated patients with severe haemophilia B (FIX:C ≤ 2%). After a washout period ≥7 days following the last PK performed with AlphaNine ® after a dose of 65–75 IU kg −1, an identical PK study was performed with BeneFIX ® on 22 of the same patients. Venous blood samples for analysis were taken at baseline and at 0.25, 0.5, 1, 3, 6, 9, 24, 48, 72 and 74 h post infusion. The outcomes of the comparison of the PK parameters were as follows: Mean (±SD) in vivo recovery (IVR) was 1.3 ± 0.4 IU dL −1 per IU kg −1 for AlphaNine ® and 1.0 ± 0.3 IU dL −1 per IU kg −1 for BeneFIX ® ( P < 0.01). Mean terminal half‐life, mean residence time, area under the curve, clearance and volume of distribution of BeneFIX ® were 36.0 ± 12.8 h, 39.3 ± 13.9 h, 1631 ± 467 IU h dL −1, 0.046 ± 0.01 dL kg −1 min −1 and 1.75 ± 0.52 mL kg −1 respectively. These values were not significantly different to those observed in AlphaNine ®, although BeneFIX ® displayed higher than expected IVR values and lower than expected clearance values. In conclusion, AlphaNine ® showed a comparable half‐life, but an IVR significantly higher than that of BeneFIX ® . This dissimilarity may have implications on dosing requirements for on‐demand treatment regimes affecting optimal resource allocation.